The Influence of Location, Promotion and Quality of Service Factors on The Customer's Decision To Choose Murabahah Financing At The Branch Office of BPRS Al Salaam Amal Salman Depok - Anisa Ikhtiaty Mubarokah (Jurnal Ilmiah Ekonomi Islam, 2022)
Murabaha financing is one of the most sought after financing by the people of Indonesia. Therefore, it is important to know what factors influence the community in choosing murabahah financing to meet their needs. So, the purpose of this study was to determine whether the factors of location, promotion, and quality of service affect customer decisions in choosing murabahah financing. This research includes quantitative research with sampling technique is probability sampling. The data processing and analysis techniques used are descriptive statistical analysis, classical assumption test, F test, t test, Adjusted R square test, and multiple linear regression analysis using SPSS Statistic 25. The results of the study that have a significant effect on customer decisions to choose murabahah financing are factors location and quality of service based on the results of tcount = 5.395 > from ttable 1.987 and tcount = 6.603 > from ttable 1.987. While the promotion does not affect the customer's decision to choose murabahah financing based on the results of the value of tcount = 1.954 < from ttable 1.987.